Akuntabilitas Pemerintah Desa dalam Pengelolaan Anggaran dan Pendapatan Belanja (APBES) (Studi Kasus Desa Karang Jaya Kecamatan Teras Terunjam Kabupaten Mukomuko) - Ida Nur Safitri; Herlin Herlin; Abdul Rahman (Politeknik Raflesia Press, 2025)
The purpose of this research is to see and know the accountability of the village government in managing the APBDes in Karang Jaya Village, Terrace Terunja Sub-district, Mukomuko Regency. This research uses a combination method that combines two methods, the techniques used are interviews, questionnaires, and documentation. The results of the study found that the accountability of the village government in managing APBDes from the planning stage to accountability, has been very bankable and I have never experienced difficulties and been caught in a case. The stages of APBDes management can be said to be very good and accountable in accordance with the rules and refer to the draft APBDes program that has been prepared. Furthermore, this draft program is the basis for the preparation of village regulations regarding the APBDes. The stages of APBDes village financial management are: 1) Planning, 2) Implementation, 3) Administration, 4) Reporting, 5) Accountability. The village government fully refers to the technical guidelines from the Regent and Permendagri No. 20/2018. Keywords: Accountability, APBDes Management, Permendagri No. 20/2018.